ANALISIS KANDUNGAN GIZI, INDEKS GLIKEMIK DAN BEBAN GLIKEMIK PRODUK IMUKAL - Jasmine Ramadina Djumantara (2020)
The Indonesian National Army (TNI) is an apparatus of national defense that has many tasks in the field. In carrying out their duties, every TNI soldier is required to have good and excellent health. During their duties in the field, TNI soldiers needed food that was easy and fast to consume and was dense in energy. This study aims to determine the nutrient content, glycemic index and glycemic load contained in imukal products as a special drink for the TNI. The method used in this research was experimental study design. The respondent's blood glucose level was examined after consuming a standard food in the form of pure glucose and a test food in the form of imukal products. The results of the analysis of nutritional content were obtained in each imukal product packaging (35 gr) containing 0.89 grams of water, 1.03 grams of ash, 3.11 grams of protein, 6.04 grams of fat, 23.93 grams of carbohydrates, and 162.48 kcal energy. After collecting and processing data, the average values of the glycemic index and the glycemic load are obtained. The glycemic index of imukal products is 89,98 (SD ± 28,55) which is included in the high glycemic index category. While the glycemic load of imukal products is 21,53 (SD ± 6,83) is included in the high glycemic load category.